Recent advances in nanomaterial-based drug delivery systems for melanoma therapy - Rabinarayan Parhi; Partha Pratim Kaishap; Goutam Kumar Jena (International Association of Physical Chemists (IAPC), 2023)
Background and Purpose: Safe and effective drug delivery is crucial for the treatment of cancer, which is quite impossible to achieve through traditional methods. Among all types of cancer, skin melanoma is known for its aggressive metastasizing ability and an unprecedented higher degree of lethalness, limiting the overall therapeutic efficacy. Here, we focus on the different types of nanomaterials (NMs) and their drug delivery applications against melanoma. Experimental Approach: All relevant publications, including research papers, reviews, chapters and patents, were assessed using search engines such as Scopus and PubMed, up to the end of August of 2023. The keywords used in the search were: nanomaterials, melanoma, drug delivery routes for melanoma, and nanomaterial-based drug delivery systems (DDS). Most of the publications out of 234 cited in this review are from the last five years. Key Results: The recent advancement and mechanism of action of various NMs against melanoma, including inorganic metallic and carbon-based NMs, organic polymeric and lipid-based NMs, and cell-derived vesicles are discussed. We also focus on the application of different NMs in the delivery of therapeutic agents for melanoma therapy. In addition, the skin and melanoma, genetic mutation and pathways for melanoma, conventional treatment options, and delivery routes for therapeutic agents are also discussed briefly. Conclusion: There are few NM-based DDS developed in the lab set up recently. The findings of this review will pave the path for the development of NM-based DDS on an industrial scale and help in the better management of skin melanoma.